Improvement of low grade ejaculates of Holstein Friesian crossbred bulls by different filtration techniques for cryopreservation - BHAKAT, M; MOHANTY, T K; GUPTA, A K; KUMAR, R; SHIVAHRE, P R; ABDULLAH, M (The Indian Journal of Animal Sciences, 2016)
To improve the quality of poor ejaculates, sephadex (FS) and sephadex with ion-exchangers (FS+IE) filtration were used to examine split samples of 18 ejaculates of 6 Karan Fries bulls at various stages of cryopreservation. Data were analyzed using analysis of variance. All semen quality traits improved in both the filtration and further superiority of FS+IE column was observed due to its better efficacy of trapping immotile, dead and abnormal spermatozoa as well as there was decrease in sperm concentration, tail and total abnormalities. The initial, prefreeze and post-thaw motility, viability, sperm cells with intact plasma membranes and sperms with normal acrosomes of FS+IE filtrates were significantly better than the nonfiltered and FS filtered semen samples during different stages of cryopreservation. Therefore, it can be concluded that better quality semen can be harvested from poor ejaculates through FS+IE and FS filtration to improve fertilization potential of the spermatozoa.